RELATIONSHIP BETWEEN LIFESTYLE, BMI STATUS, AND LEVEL OF RELIGIOUS KNOWLEDGE RELATED TO MENARCHE AND EARLY MENARCHE IN ELEMENTARY SCHOOL X CHILDREN IN SOUTH TANGERANG CITY IN 2022 - Apipah Auliah Nasution; Nurfadhilah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
With a decrease in age of 0.145 years every decade, Indonesia ranks 15th out of 67 countries according to the results of the 2010 RISKESDAS report, which found that 5.2% of children in 17 provinces in Indonesia experienced menarche before the age of 12 which was characterized by enlarged pelvis, breast enlargement, growth of axillary hair and pubic hair. Menarche has occurred in 20.9% of Indonesian women under the age of 12 years. The study design was cross-sectional with a sample of 90 children in grades 5 and 6. The sampling technique used non-probability sampling, data analysis used the Chi-Square test (α=0.05). Variables related to the incidence of early menarche are lifestyle (P-value=0.004, OR=9.008), BMI status (P-value=0.007, OR=8.042), variables not related to early menarche, namely: level of religious knowledge related to menarche (P-value=1.000, OR=0.000). This research is expected to provide additional insight to the public regarding early menarche. This research is expected to be literacy to complement previous studies regarding early menarche. Future research can add other variables that have not been discussed in this study, such as nutritional status or others.